Kode Etik Netizen Muhammadiyah: Implementasi dan Respon NetizenMu di Lampung - Sutarno, Sutarno; Mardicko, Afri (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2021)
This article aims to describe how Muhammadiyah netizens (netizenMu), the mellinials in particular, respond to the code of ethics of Muhammadiyah netizens and how they implement the code of ethics. This study used mixed-methods, quantitative and qualitative, with a case study approach. Data collection was carried out through questionnaires distributed to 349 respondents and observations on respondents' online activities on 70 Facebook accounts, and interviews to them as well. The findings have revealed that the majority of netizenMu respond positively to the code of ethics of Muhammadiyah netizens and implemented it well. It can be seen from their response that the majority of respondents have answered ‘very often’ and ‘often’ in almost all the items of questionnaires.